2020
DOI: 10.3390/ani10020195
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Digestion of Chestnut and Quebracho Tannin Extracts: Antimicrobial Effect, Antioxidant Capacity and Cytomodulatory Activity in Swine Intestinal IPEC-J2 Cells

Abstract: Quebracho (Qu) and chestnut (Ch) are natural sources of tannins and they are currently used in animal nutrition as feed ingredients. However, to date the bio-accessibility, antimicrobial, antioxidant, and intestinal epithelial cell stimulatory doses of Qu and Ch have not been determined. Our study investigates the antioxidant and E. coli F4+ and F18+ growth inhibitory activity of Qu, Ch, and their combinations after solubilization in water (to evaluate the already bio-accessible molecules) and after simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 35 publications
(36 reference statements)
3
36
0
Order By: Relevance
“…In fact, the combined effect of Ch/Qu tannins could be exacerbated during stressful conditions, such as experimental bacterial infections [ 24 , 28 ]. According to Reggi et al [ 16 ], beneficial effects were reported when Ch/Qu digesta were administered to experimentally stressed intestinal swine cells, suggesting that it might have a trophic effect at the intestinal epithelium, and an increased viability of cells was observed after tannin treatment. In present study, animals were reared in a conventional herd farm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, the combined effect of Ch/Qu tannins could be exacerbated during stressful conditions, such as experimental bacterial infections [ 24 , 28 ]. According to Reggi et al [ 16 ], beneficial effects were reported when Ch/Qu digesta were administered to experimentally stressed intestinal swine cells, suggesting that it might have a trophic effect at the intestinal epithelium, and an increased viability of cells was observed after tannin treatment. In present study, animals were reared in a conventional herd farm.…”
Section: Discussionmentioning
confidence: 99%
“…The Ctrl and Ch/Qu diets adopted in the in vivo trial were in vitro digested using the protocol reported by Reggi et al [ 16 ]. The in vitro digestion was performed according to the protocol described by Regmi et al [ 38 ] with minor adaptations previously reported by our group [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a crude extract of chestnut had stronger antibacterial properties than purified vescalagin and castalagin, probably due to the synergy exerted by the molecules contained in the extract [ 42 ]. Finally, C. sativa extracts have been reported to inhibit E. coli and Clostridium perfringens growth when applied at 1200 µg/mL and 3–150 µg/mL, respectively [ 43 , 93 ].…”
Section: Biological Activities Of Tannin-rich Extractsmentioning
confidence: 99%